TEORI ISTIHALAH MENURUT PERSPEKTIF ISLAM DAN SAINS: APLIKASI TERHADAP BEBERAPA PENGHASILAN PRODUK MAKANAN - Jamaludin, Mohammad Aizat (Jurnal Syariah, 2009)
Basically, this article focuses on the theory of istihalah from both Islamic and modern science perspectives. It involves discussions on the application of istihalah in several food products, whether it is classified as istihalah sahihah (acceptable change) or istihalah fasidah (unacceptable change). In order to achieve the objective, samples of animal-based food products are used to analyse the theory of istihalah. The research finding shows that istihalah is relevant as a purification alternative to solve the recent issues on food product.